2010
DOI: 10.1039/c0an00525h
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy differentiates between multipotent and pluripotent stem cells

Abstract: Over the last few years, there has been an increased interest in the study of stem cells in biomedicine for therapeutic use and as a source for healing diseased or injured organs/tissues. More recently, vibrational spectroscopy has been applied to study stem cell differentiation. In this study, we have used both synchrotron based FTIR and Raman microspectroscopies to assess possible differences between human pluripotent (embryonic) and multipotent (adult mesenchymal) stem cells, and how O(2) concentration in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…The validation set from the differentiation of the hiPSC line, IMR90C2 was found to classify at 100%, 93% and 80% for the BMP4/ACTIVIN A, FGF2, and undifferentiated groups respectively, and their specificities that were obtained were 100%, 97% and 100% (Supplementary Figure 2F). The finding that lipid stores diminished during the loss of pluripotency by hiPSCs corroborates hESC differentiation data previously published by our laboratory and other groups [11,15]. The reasons why lipid depletion occurs during the differentiation process is unclear but one group has suggested that the eicosanoid pathway may play an important role [36].…”
Section: Undifferentiated Human Embryonic Stem Cells and Human Inducesupporting
confidence: 90%
See 1 more Smart Citation
“…The validation set from the differentiation of the hiPSC line, IMR90C2 was found to classify at 100%, 93% and 80% for the BMP4/ACTIVIN A, FGF2, and undifferentiated groups respectively, and their specificities that were obtained were 100%, 97% and 100% (Supplementary Figure 2F). The finding that lipid stores diminished during the loss of pluripotency by hiPSCs corroborates hESC differentiation data previously published by our laboratory and other groups [11,15]. The reasons why lipid depletion occurs during the differentiation process is unclear but one group has suggested that the eicosanoid pathway may play an important role [36].…”
Section: Undifferentiated Human Embryonic Stem Cells and Human Inducesupporting
confidence: 90%
“…At present, there is only a limited body of literature reporting the application of FTIR microspectroscopy in the study of embryonic and adult stem cells [11][12][13]. Furthermore, the only extant study using FTIR to classify human iPSCs [14] has been restricted to undifferentiated cells, where as iPSC derived lineage committed progeny progenitors have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…With the inherent weakness of the signal in the Raman imaging mode, stemming from the low probability of Raman shifted scattered photons, a number of approaches have been proposed to boost the signals or increase speci¯city by using either Raman tags 26 or nanoparticles. 27,28 However, even with the inherent technical di±-culties from low signal levels, Raman imaging where the entire spectra is captured (known as spontaneous Raman imaging) is capable of classifying cell types, 29 locating regions of activity in a cell 30 and determining the dynamic changes in molecular distribution in a living cell without labeling. 31,32 In practice, a subset of molecules in the sample exhibit some overlap between the incident light photon energy and the electronic excitation states of the molecule.…”
Section: Spectroscopic Methodsmentioning
confidence: 99%
“…Researchers have been able to successfully differentiate between various cell types solely based on their intrinsic characteristic Raman peaks, which are due mostly to differences in the composition of DNA, protein, and lipids within the cells. This differentiation includes discerning certain cancer cells from normal cells (3) and even the differences between human embryonic and adult mesenchymal stem cells (4). In addition, researchers have been able to use Raman microscopy imaging to localize the intracellular distribution of metabolites and metabolic changes induced by certain therapeutic drugs.…”
Section: In Vitro Raman Imaging In Cell Studies Intrinsic Approachmentioning
confidence: 99%